Pemodelan Pertumbuhan E-Commerce di Indonesia dengan Spatial Autoregresive Model (SAR) - Purwanti, Yuniasih (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2023)
The development of information technology has had a significant impact on the growth of e-commerce in Indonesia. However, the distribution of e-commerce is still concentrated in Java and Sumatera. It shows the inequality of the distribution of the e-commerce industry. Therefore, this study attempted to model the growth of e-commerce by considering the effect of dependence between regions. The variables use in this study included economic growth, base transceiver station (BTS), computer use, cellular phone ownership and the availability of strong signals (4G). The methods used were the Spatial Autoregressive Model (SAR) and the Spatial Error Model (SEM). The study's results showed that the SAR model was better than the SEM model. In addition, the test results indicated an autocorrelation relationship between provinces, which means that the growth of e-commerce in a province will be followed by an increase in e-commerce in the surrounding region. Meanwhile, the e-commerce growth in a province was affected by BTS, computer and telephone use, the availability of strong signals, and spatial residuals from other provinces that are close to each other.